Cyber journalism: bridging the gap between professionalism and epistemology / Faridah Ibrahim - Ibrahim, Faridah (CMIWS and UiTM Press, 2011)
Cyber journalism is a term coined following the convergence of various traditional media brought about by the proliferation of media industries due to current influx of new technology and globalisation. Cyber journalism is made possible by the internet technology and globalisation. Cyber journalism has gained importance over the past years and new terms are attached to it - some popular ones are internet journalism, online journalism, blogs and citizen journalism. Cyber journalism is functioning as a pervasive medium along with the traditional media such as print and electronic. However, cyber journalism has created a big vacuum in journalism education and training since it is a recent development in journalism and journalism educators are caught unprepared. Whilst journalism educators are well groomed and prepared towards the epistemology of journalism education and well aware of the demands of professionalism in the real world, the emergence of cyber journalism has brought new challenges to schools offering journalism courses. Journalism educators have to strike a balance between the demands of new journalism knowledge and professionalism. Furthermore with the onset of new technologies, the definition of cyber journalist has gone beyond the realm of journalistic education. Anybody who is techno-savvy can become a cyber-journalist. The question of epistemology, professionalism, responsibility and credibility have now become an epitome of cyber journalism. This paper will discuss the fundamentals of cyber journalism and strategies in bridging the gap between professionalism and the epistemology.